Evaluation of interprofessional health care team communication simulation in geriatric palliative care. Issue 1 (2nd January 2019) - Gellis, Zvi D.; Kim, Eunhae; Hadley, Diane; Packel, Lora; Poon, Cathy; Forciea, Mary Ann; Bradway, Christine; Streim, Joel; Seman, John; Hayden, Tara; Johnson, Jerry
ABSTRACT: An interprofessional education (IPE) simulation-based geriatric palliative care training was developed to educate health professions students in team communication. In health care, interprofessional communication is critical to team collaboration and patient and family caregiver outcomes. Studies suggest that acquiring skills to work on health care teams and communicate with team members should occur during the early stage of professional education. The Interprofessional Education Collaborative (IPEC®) competency-based framework was used to inform the training. An evaluation examined attitudes toward health care teams, self-efficacy in communication skills, interprofessional collaboration, and participant satisfaction with the training experience. One-hundred and eleven participants completed pre- and post-training surveys. Overall, a majority of participants (97.3%) were satisfied with the training and reported more positive attitudes toward health care teams and greater self-efficacy in team communication skills. IPE participants had higher collaboration scores compared to observer learners. Further research is needed to explore long-term effects of IPE in clinical practice.